The Macedonian conflict : ethnic nationalism in a transnational world - Danforth, Loring M., 1949- (Princeton University Press, 1995)
Greeks and Macedonians are presently engaged in an often heated dispute involving competing claims to a single identity. Each group asserts that they, and they alone, have the right to identify themselves as Macedonians. Loring Danforth examines the Macedonian conflict in light of contemporary theoretical work on ethnic nationalism, the construction of national identities and cultures, the invention of tradition, and the role of the state in building a nation. The conflict is set in the broader context of Balkan history and in the more narrow context of the recent disintegration of Yugoslavia.